About the Semantics of the Femicide in Chile - Cáceres Pérez, Daniela Isabel (Sociedad y Economía, 2016)
In 2006 a new concept starts to be inserted on the semantics of the Chilean society, a constant count of murder of women visualizes a social problem: femicide. Thus, feminist organizations and supranational organizations with right approach have put their efforts in theming femicide and demand the state intervention in prevention policies. In this context, in 2007 in Chile the motion that defines the legal concept of femicide is proposed.This article, based on an empirical research, tries to investigate the semantization of femicide in Chile, considering the path to its enactment. Also, the problem of femicide will be exposed as a result of gender violence in the context of a patriarchal society, to finally, in this scenario, to understand how the concept disseminated its meaning, as a law, in the population.